일부 대학생의 악안면외상경험과 측두하악장애 유병상태와의 관련성 - 전은숙(Eun-Suk Jeon); 이정화(Jung-Hwa Lee) (한국콘텐츠학회 논문지, 9(7), 2009)
This study was to investigate the relation between maxillofacial trauma experience and temporomandibular disorder prevalence with a view to helping prevent and cure temporomandibular dysfunctions by conducting a questionnaire survey with 370 students attending C Health Care College located in Ulsan Metropolis. Data collected underwent an analysis using SPSS program, resulting in the following:1. As for TMJ(temporomandibular joint) clicking prevalence rate, with 25.7% of male students and 22.7% of female students answering positively, the former showed higher rate of temporomandibular joint clicking (p<0.01), while no significant difference was identified depending on school years. 2. In terms of temporomandibular pain prevalence rates, females were found to have been more affected than male students. 3. When it comes to trismus prevalence rates, 10.8% of female students and 7.0% of male students responded they had experienced the dysfunction and female students showed slightly higher rate of trismus prevalence. 4. 6.5% of males and 4.3% of female students responded they had got treatment experience resulting from temporomandibular disorders, indicating that more male students had gone through treatment for temporomandibular disorders(p<0.05). 5. Male students showed higher experience rate of maxillofacial trauma(p<0.01), mostly due to falling or tumbling down, followed by exercises and etc. 6. The relation between maxillofacial trauma and temporomandibular disorders showed statistically significant relation between maxillofacial trauma and TMJ(temporomandibular joint) clicking (p<0.01). 이 연구는 악안면외상경험과 측두하악장애 유병상태와의 관련성을 조사하여 측두하악장애의 예방과 치료계획에 도움을 주고자 울산광역시에 소재한 C보건대학 학생 370명을 대상으로 설문조사를 실시하였다. 수집된 자료는 SPSS 프로그램을 이용하여 분석하여 다음과 같은 결론을 얻었다. 1. 측두하악관절잡음 유병률은 남학생 25.7%, 여학생 22.7%로 남학생이 측두관절잡음 발생이 높았으나(p<0.01), 학년별로는 유의한 차이를 보이지 않았다. 2. 측두하악동통 유병률은 여학생이 높게 나타났다. 3. 개구장애 유병률은 여학생 10.8%, 남학생 7.0%로 여학생이 개구장애 발생이 약간 높게 나타났다. 4 측두하악장애로 인한 치료 경험은 남학생 6.5%, 여학생 4.3%로 남학생이 측두하악장애 치료경험률이 높게 나타났다(p<0.05). 5. 악 안연외상 경험률은 남학생이 높게 나타났으며(p<0.01), 악안면외상 경험 경로 중 넘어짐이 가장 많았으며, 운동, 기타 순으로 나타났다. 6. 악안면 외상과 측두하악장애와의 관련성은 악악면외상과 측두하악관절잡 음 간에 통계적으로 유의한 관련성을 보였다(p<0.01). 이상의 결과 악안면외상 경험유무와 측두하악장애 간에는 관련성이 존재하며 악안면외상을 측두하악장애 발생의 기여요인으로 볼 수 있겠다. 따라서 향후 측두하악장애를 일으키는 요인이 무엇인지 그 관련요인에 대한 추가연구가 필요하다고 사료된다.